Effect of Fish Oil, Virgin Coconut Oil, and Used-Cooking Oil Consumption on Hematological Profile in Mice - Mas Rizky A.A. Syamsunarno; Dinar F. Agustin; Neni Anggraeni; Nia Kania (Universitas Padjadjaran, 2020)
Humans require macronutrients and micronutrients to fulfill daily energy requirements, and triglyceride is a notable example, belonging to the fat family. This is particularly consumed frequently, and is composed of glycerol, and the fatty acid, specifically differentiated into unsaturated, saturated, trans, and cis forms. Furthermore, these constituents are known to play many roles in the body, including in the hematopoietic process. This involves oxidation and consequently stem cell differentiation into many blood cells in long-term, although the effect short-term is currently unknown. The study aimed, therefore, to investigate the effect of short-term intake of different fatty acid types on hematological profile in an animal model, conducted at the Animal Laboratory, Universitas Padjadjaran in October 2018. In addition, each group comprised 6 mice, orally administered distilled water as control (Group A), fish oil (Group B), virgin coconut oil (Group C), and used-cooking oil (Group D), at a dose of 5 μl/g body weight/day for 2 weeks. Subsequently, analysis was performed using blood measurement with hematology analyzer. The results showed lower white blood cell (WBC) count in Group B compared to D (p<0.05), alongside lymphocyte count (p<0.01). Moreover, the WBC in Group C was lower than D (p<0.01), also observed in lymphocyte count (p<0.001), % lymphocyte (p<0.01), while the % granulocyte count was higher than group D (p<0.01). Therefore, the highest total leukocyte and lymphocyte number among the other groups, as well as higher percentage of differential lymphocyte count was observed with mice provided with used-cooking oil compared to coconut oil, alongside a lower percentage of differential granulocyte count (p<0.05). However, fatty acid intake in group A, B, C, and D had no significant impact on RBC and platelet parameters. In conclusion, used-cooking oil induces a change in hematological profiles compared to fish oil and virgin coconut oil, featuring the increased total white blood cells and lymphocyte, as well as reduced % granulocyte.Keywords: Fatty acid, hematological profile, leucocyte Efek Pemberian Minyak Ikan, Minyak Kelapa Murni, dan Minyak Jelantah Terhadap Profil Hematologi MencitAbstrakManusia membutuhkan makronutrien dan mikronutrien untuk memenuhi kebutuhan energi harian. Salah satu sumber makronutrien adalah trigliserida yang merupakan salah satu jenis lemak yang paling sering dikonsumsi. Senyawa ini tersusun atas asam lemak dan gliserol. Terdapat banyak jenis asam lemak seperti asam lemak jenuh, asam lemak tidak jenuh, asam lemak trans, dan asam lemak cis. Rantai asam lemak memiliki banyak peran dalam tubuh, salah satunya adalah hematopoiesis sel stem. Pada konsumsi lemak jangka panjang, hematopoiesis ini terjadi melalui oksidasi asam lemak yang selanjutnya akan menstimulasi diferensiasi sel stem menjadi sel-sel darah di perifer, tetapi efeknya dalam jangka pendek belum diketahui. Oleh karena itu, penelitian ini bertujuan untuk menginvestigasi efek jangka pendek dari konsumsi berbagai jenis asam lemak terhadap profil hematologi mencit yang dilakukan di Laboratorium Hewan, Universitas Padjadjaran pada Oktober 2018. Mencit diberikan air suling sebagai kontrol (Grup A), minyak ikan (Grup B), minyak kelapa murni (Grup C), dan minyak jelantah (Grup D) dengan dosis 5μl/g berat badan/hari secara oral selama dua minggu. Profil hematologi diukur menggunakan hematology analyzer. Hasilnya, grup B memiliki jumlah leukosit lebih rendah dibandingkan grup D (p<0,05) dan limfosit yang lebih rendah dibandingkan grup D (p<0,01). Grup C memiliki jumlah leukosit lebih rendah dibandingkan grup D (p<0,01), jumlah limfosit yang lebih rendah dibandingkan grup D (p<0,001), % limfosit lebih rendah dibanding grup D (p<0,01), dan % granulosit lebih tinggi dibanding grup D (p<0,01). Selain itu, konsumsi asam lemak pada grup A, B, C, dan D tidak memengaruhi indeks RBC dan platelet secara signifikan. Sebagai simpulan, minyak jelantah memberikan efek terhadap perubahan profil hematologi mencit dibandingkan minyak ikan dan minyak kelapa murni, yaitu meningkatkan leukosit dan limfosit dan menurunkan % granulosit.Kata kunci: Asam lemak, leukosit, profil hematologi